Evaluation of User Satisfaction E-XYZCash Application at PT Bank XYZ Using Technology Acceptance Model - Agny Monica Candraputri, Albert Cahyadi Gunawan, Fathan Abdussalam, Gunawan Wang, Sfenrianto (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to identify user satisfaction of e-XYZcash, mobile application in PT. Bank XYZ. This research method used is Technology Acceptance Model (TAM) that have been modified, which belongs to Davis F. D. and analyzed using Structural Equation Model (SEM), aided by Smart Partial Least Squares (SmartPLS) application to connect between variable each model. This research was based on user satisfaction of e-XYZcash, mobile application and the result can be used as reference or learning. There are two insignificant factors and four factors that are significant for the e-XYZcash application. Keywords: Evaluation, Mobile Application, System, Technology Acceptance Model, SEM – PLS